UPAYA PONDOK PESANTREN DALAM PEMBERDAYAAN MASYARAKAT SEKITAR HUTAN - M. Bashori - Muchsin; Yuli Andi Gani; M. Irfan - Islamy (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT Empowerment of societies living near the Sumberingin forest by the Sanan Gondang pesantren is to enhance quality of the santris. The quality improvement involving the psychological and physical aspects. The former encountered the five forms of moral persistence as follows : (1) ikhlas is the sincere sacrifice for the success of a task; (2) I’tidal is the very straightforward and honest attitude; (3) alwasatoh is the balanced attitude in making decisions; (4) istiqomah is the stability in conducting continous and tiresome tasks with high persistence, patience and endurance; (5) tawakkal, is the awareness of one’s limited capability by introspection. In physical terms, sent santris to the Ketu Forest Farming Training Centre in Surakarta, will enhance skills of santris and farmers in farming arrow root under the teakwood and Kosambi trees. These agrotechnological skills were passed on farmers involved in the Wanatani Project at the Sumberingin village. Results show that the Sanan Gondang pondok pesantren enhanced quality of santris and farmers in empowering any societies residing around forest-area in the Sumberingin village, Sanan Kulon district, Blitar. Quality improvement of santris involved (1) the awareness that the Wanatani Project is a service of loyalty, (2) the organizational and leadership skills, and (3) farming techniques of planting arrow root under teakwood and Kosambi trees. The enhancement of the quality of farmers involved (1) the socialization of planting arrow root under the teakwood and Kosambi trees involving the Village Head and the RW-RT, (2) the extension and practice of arrow root planting under teakwood and Kosambi trees as an intercropping system, (3) encouraging and motivating the farmers to work hard to succeed the arrow root planting under teakwood and Kosambi trees, and (4) continuous reciting (wirid) of the kursy verses and sholawat readings. Keywords: pondok pesantren, forest areas, empowerment